Nowogródek – historia sztetlu - Bauer, Yehuda (Zagłada Żydów. Studia i Materiały, 2007)
The article deals with the history of the shtetl in Nowogródek, where, before the war about 6,500 Jews lived. When the Germans occupied Nowogródek, a ghetto was established in one of the suburbs, where all the local Jews were deported. The author describes everyday life of the Jews in the ghetto and their fate. Most of them were killed in three mass executions: in December 1941, in August 1942 and February 1943. Many managed to escape to the Bielski partisan outfit, operating in the nearby Nalibocki Forest; the most spectacular escape was that of 232 Jews through a tunnel. These Jews had remained in the town after the mass executions.